Elections, Ethnicity, and Political Instability. (September 2017) - Butcher, Charles; Goldsmith, Benjamin E.
This article provides a new perspective on the impact of elections on violent political instability in ethnically divided states. A number of scholars argue that elections may provoke large-scale violence in ethnically divided states. In this article, we theorize that elections have a pacifying effect in the most ethnically fractionalized countries as they reduce endemic uncertainty and encourage coalition building, lowering the rate at which electoral losers discount the future. Probit regressions using cross-national data for the period 1960-2010 support the notion that instability onsets are less likely in ethnically fractionalized states during election periods, and especially in the year after a national election.